Long-term mortality and incidence of cardiovascular diseases and type 2 diabetes in diabetic and nondiabetic obese patients undergoing gastric banding: a controlled study. Issue 1 (December 2016) - Pontiroli, Antonio; Zakaria, Ahmed; Mantegazza, Ermanno; Morabito, Alberto; Saibene, Alessandro; Mozzi, Enrico; Micheletto, Giancarlo
Abstract Background and aim Aim of this retrospective study was to compare long-term mortality and incidence of new diseases [diabetes and cardiovascular (CV) disease] in morbidly obese diabetic and nondiabetic patients, undergoing gastric banding (LAGB) in comparison to medical treatment. Patients and methods Medical records of obese patients [body mass index (BMI) > 35 kg/m2 undergoing LAGB (n = 385; 52 with diabetes) or medical treatment (controls, n = 681; 127 with diabetes), during the period 1995–2001 (visit 1)] were collected. Patients were matched for age, sex, BMI, and blood pressure. Identification codes of patients were entered in the Italian National Health System Lumbardy database, that contains life status, causes of death, as well as exemptions, drug prescriptions, and hospital admissions (proxies of diseases) from visit 1 to September 2012. Survival was compared across LAGB patients and matched controls using Kaplan–Meier plots adjusted Cox regression analyses. Results Observation period was 13.9 ± 1.87 (mean ± SD). Mortality rate was 2.6, 6.6, and 10.1 % in controls at 5, 10, and 15 years, respectively; mortality rate was 0.8, 2.5, and 3.1 % in LAGB patients at 5, 10, and 15 years, respectively. Compared to controls, surgery was associated with reduced mortality [HR 0.35, 95 % CI 0.19–0.65, p < 0.001 at univariate analysis, HR 0.41, 95 % CI 0.21–0.76, p < 0.005 at adjusted analysis], similar in diabetic [HR 0.34, 95 % CI 0.13–0.87, p = 0.025] and nondiabetic [HR 0.42, 95 % CI 0.19–0.97, p = 0.041] patients. Surgery was also associated with lower incidence of diabetes (15 vs 48 cases, p = 0.035) and CV diseases (52 vs 124 cases, p = 0.048), and of hospital admissions (88 vs 197, p = 0.04). Conclusion Up to 17 years, gastric banding is associated with reduced mortality in diabetic and nondiabetic patients, and with reduced incidence of diabetes and cardiovascular diseases.